Preparing Principals to Raise Student Achievement Implementation and Effects of the New Leaders Program in Ten Districts - Gates, Susan M. (RAND Corporation, 2014)
New Leaders is a nonprofit organization that partners with school districts to prepare and support principals. This report describes how the New Leaders program was implemented in partner districts, and it provides evidence of the effect that New Leaders has on student achievement.